Gambaran Deteksi Dini Diabetes Melitus Tipe 2 pada Agregat Dewasa - Devina Jenamo, Ida Ayu; Achjar, Komang Ayu Henny; Gama, I Ketut; Lestari, Agus Sri; Ngurah, I Gusti Ketut; Harini, I Gusti Ayu (Jurnal Gema Keperawatan, 2024)
Early adulthood is a continuation of youth, so the identity of early adulthood is not much different from youth. Type 2 diabetes mellitus is a metabolic disorder characterized by elevated blood sugar due to decreased insulin secretion. In addition to diabetes mellitus, this disease is a global health problem that is the leading cause of death and a major contributor to the high morbidity rate in Indonesia. Urbanization leading to lifestyle changes, and migration from rural to urban areas are two environments hypothesized to increase the incidence of type 2 DM. Type 2 diabetes will start as a result of obesity. The purpose of this study was to determine how the overview of early detection of non-communicable diseases in adults. The research design is descriptive research. The population of this study was 124 people with a sample of 95 people taken with non-probability sampling technique, namely purposive sampling. Data collection instruments in this study used a glucometer to measure blood sugar during. Research results 95 respondents obtained early detection of diabetes mellitus in adults in Banjar dinas Taman Griya Jimbaran Environment with a normal majority of 60 people (63,2%), high as many as 20 people (21,1%) and low as many as 15 people (15,8%). Suggestions are expected that respondents will continue to emphasize healthy living and avoid fast food to combat diabetes mellitus.